The Union Club. - Gillray, James, 1756-1815 (Humphrey, H., 1801)
Scholarly notes may be added at a later date.
1 print : col.
Keywords: Caricatures; Cartoons; Great Britain -- Politics and government -- 1800-; Ireland -- History -- Union, 1801